0
$\begingroup$

Let $t \in \mathbb{Z}$. Let $p$ and $q$ be primes, and let $N = p \cdot q$.
Prove that $(t$ mod $N) $ mod $ p = (t$ mod $p)$

I found this question on some website. Intuitively I can easily understand that it's true and also explain it in words, but I can't find a formal proof for it. Help would be appreciated!

$\endgroup$
1
$\begingroup$

Hint: let $t = a p +b$ with $0 \le b \le p-1\,$, so that $t \bmod p = b\,$. Then let $a = cq+d$ with $0 \le d \le q-1\,$, so that $t = cpq+dp+b\,$. It follows that $t \bmod pq = dp+b\,$ (why?), so in the end $(t \bmod pq) \bmod p = (dp+b) \bmod p = b $.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.